(untitled) (Physical Education, Health and Social Sciences, 2025)
Background: Gastroesophageal reflux disease (GERD) is a prevalent chronic gastrointestinal disorder with a rising global burden. However, data on GERD prevalence and associated lifestyle and dietary risk factors in Sindh, Pakistan, are limited. This study aimed to estimate the prevalence of GERD and identify its associated sociodemographic, lifestyle, and dietary factors among adults attending gastroenterology outpatient clinics in Hyderabad, Sindh. Methods: A hospital-based cross-sectional study was conducted from January to May 2023 among adults aged ≥18 years attending gastroenterology outpatient departments of tertiary care hospitals in Sindh. Data were collected using a structured questionnaire covering sociodemographic characteristics, lifestyle and dietary habits, and the Frequency Scale for the Symptoms of GERD (FSSG). GERD was defined as an FSSG score ≥8. Associations were analyzed using chi-square tests, and independent predictors were identified through multivariate binary logistic regression using SPSS version 23. Results: A total of 601 participants were analyzed, with a GERD prevalence of 48.9% (n = 294). GERD was significantly associated with male gender, increasing age, lower educational status, and middle economic status (p < 0.05). Lifestyle and dietary factors, including physical inactivity, frequent consumption of junk food, meat, tea, and soft drinks, showed significant associations with GERD. Multivariate analysis identified male gender, older age, lower education level, economic status, family size, and junk food consumption as independent predictors of GERD. Conclusion: GERD was highly prevalent among adults attending gastroenterology outpatient clinics in Sindh. Several modifiable lifestyle and dietary factors were independently associated with GERD, underscoring the need for targeted preventive and behavioral interventions.